Encyclopedia of Science Education
89 illus., 42 illus. in color. eReference.
Keywords: The Encyclopedia of Science Education provides a comprehensive international reference work covering the range of methodologies, perspectives, foci, and cultures of this field of inquiry, and to do so via contributions from leading researchers from around the globe. Because of the frequent ways in which scholarship in science education has led to developments in other curriculum areas, the encyclopedia has significance beyond the field of science education. The Encyclopedia of Science Education is aimed at graduate students, researchers, developers in science education and science education research. The topics to be covered encompass all areas of science education and it includes biographical entries on science educators, as well as educators whose work has had an impact on science education as a research field.